Rats, cats and hares: exploring natural and humanly-mediated dispersal through a genetic approach - Jamieson, AE (2021)
The natural world has been largely shaped by climate fluctuations throughout time. However, more recently in the earth’s history this has changed. Humans have been manipulating the world around them for millennia, including moving a variety of species within and outside of their natural ranges. This can be deliberate: such as the raising of animals for subsistence, or accidental: such as stowaway animals on ships. In order to further our understanding of where and when people have moved animals in the past this thesis explores the movements of three understudied species. It begins with the study of a species whose range has been largely shaped by natural causes, the mountain hare. It’s distribution across Europe and Russia has been shaped by the changing climate, however even with these changes, it maintained its population structure throughout its vast range through time. This thesis focuses on the western edge of the mountain hare range where it was cut off from the rest of the continuum on the edge of the ice sheet with the last advance of ice, surviving in refugia and recolonising when conditions became favourable similarly to other possible Celtic fringe species in Britain and Ireland. This demonstrates the resilience of this cold adapted species over millennia of climate fluctuation. The other two species studied were translocated by people, one intentionally and one accidently. The domestic cat was at least initially intentionally moved for pest control. The domestic cat arrived in Britain in the Iron Age and became widespread in the Roman period. It was also an early arrival in the Orkneys of Scotland in the Scottish Late Iron Age, contemporary with Roman Britain. Domestic cats then became widespread in the Viking and Norse periods of Orkney. In Ireland only two of the three domestic cat lineages were found which may demonstrate that they missed the first wave of introduction of domestic cats. The black rat was the final species investigated; they were unintentionally transferred as stowaways on boats. This research explores their initial movements into Europe in the Roman period followed by their decline, re-emergence and later decline. Studying all three species together gives us a greater breadth of understanding of the movements of animals in the past, both naturally and anthropogenically. In addition, the results of this thesis will provide information that will be useful in the conservation management of each of these species in the future.